The Utilization of Awake Flexible Bronchoscopic Intubation in Lieu of Rapid Sequence Induction in the Critically Ill: A Case Series - Al-saeed, Nawaf; Alawad, Saud; Alsaed, Mohamad; Al-Jaroushi, Hatim (Archives of Clinical and Medical Case Reports, 2025)
Background: Critically ill patients in the intensive care unit (ICU) often present with complex comorbidities and hemodynamic instability, making rapid sequence induction (RSI) for airway management potentially hazardous. Awake flexible bronchoscopic intubation (FBI) offers a safe alternative without the need for the utilization of procedural induction or in those with anticipated difficult airways. Methods: This case series describes nine ICU patients who underwent FBI due to conditional intolerance to RSI, either from hemodynamic instability requiring vasopressor support, anticipated difficult airways, or the need for subsequent bronchoscopic evaluation/management. Patient demographics, comorbidities, vasopressor requirements before and after intubation, and peri-intubation events were described. Results: All nine patients were successfully intubated on the first attempt using FBI. The cohort included individuals with significant comorbidities such as obesity (BMI up to 76), cardiovascular disease, malignancy, and respiratory failure. FBI was performed without the need for RSI, and most patients maintained stable or improved hemodynamics post-intubation. Some had reduced or no vasopressor requirement following the procedure. In addition to airway management, FBI facilitated concurrent diagnostic and therapeutic bronchoscopic interventions, including bronchoalveolar lavage and removal of airway obstructions. Conclusions: Awake FBI is a valuable technique for securing the airway in critically ill patients who are poor candidates for RSI due to hemodynamic instability or anticipated difficult airways. FBI not only reduced the risk of peri-intubation hypotension but also allows for immediate airway evaluation and intervention. These findings support the inclusion of FBI for select high-risk ICU patients.